(untitled) (Circe de clásicos y modernos, 2019)
One of the traits ancient testimonies empha-size the most about Cleon is his way to speak in public (Thuc. 3. 36. 6; [Arist] Ath. 28. 3; Theopomp. fr. 92; Plut. Nic. 8. 5), since he would have infringed a previous social norm regarding the proper way to do it (Connor 1992: 132-134). The aim of this article is to trace how Aristophanes represents Cleon regarding his body and his speech and to identify the procedures through which he does it. Our hypothesis is that we can recognize in later descriptions a ‘family resemblance’ in relation to the representation we find in the Aristophanic comedies.